Gender Differences in Motor Skills of the Overarm Throw - Gromeier, Michael; Koester, Dirk; Schack, Thomas (Frontiers in Psychology, 2017)
In this cross-sectional study, the qualitative and quantitative throwing performance of male and female athletes (six to 16 years of age) was analyzed. The goal of this study was to assess wheth-er there were gender based qualitative and quantitative differences in throwing performance of young athletes, throughout three different age bands (childhood, pubescence, and adolescence). Furthermore, we explore whether all components of the throwing movement are equally affected by gender differences. Focus was placed on five essential components of action: trunk, forearm, humerus, stepping, and backswing. Therefore, children and adolescents (N = 96) were invited to throw three times from three different distances, while aiming at a target placed at shoulder height. The participants were aspiring athletes, competitive in the sport handball. For analyzing the quality of movement the component approach of Halverson and Roberton (1984) was used. The throwing accuracy was noted and used to evaluate the quantitative performance of the throwing movement. Throughout three different age bands, no statistically significant difference was found between genders in throwing accuracy, i.e., quantitative performance. Regarding the qualitative evaluation of the throwing movement, male and female athletes differed significantly. The component approach yielded higher scores for male than for female participants. As ex-pected, with increasing age qualitative and quantitative performance of male and female athletes improved. These results suggest that there are gender-specific differences in qualitative throwing performance, but not necessarily in quantitative throwing performance. Introspection shows that differences in the qualitative throwing performance were seen in specific components of action. Male and female athletes demonstrated similar movement patterns in humerus and forearm actions, but differed in trunk, stepping, and backswing actions.